PREVALENCE AND ASSOCIATED RISK FACTORS OF TRICHOMONIASIS AMONG PREGNANT WOMEN RECEIVING ANTENATAL CARE IN AMAC, FCT ABUJA, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: Trichomoniasis is a global public health concern threatening pregnant women and female neonatal health. Aim: The study was designed to determine the prevalence and associated risk factors of trichomoniasis among pregnant women receiving antenatal care in Abuja Municipal Area Council, FCT, Abuja. Materials and Method: A cross-sectional descriptive study was employed, and 422 HVS and MSU samples were collected from pregnant women aged 20-50 years and analysed microscopically using direct wet mount. A self-structured interview questionnaire was administered to collect data on the risk factors associated with trichomoniasis.Result: The result showed that out of 422 samples tested, 97(23.0%) had the infection. Pregnant women aged 21-25 years had the highest prevalence rates of trichomoniasis with 28.9% and is relatively more (25.6%) among those in their second trimester. Educational status (χ² = 71.27, P = 0.0290), marital status (χ² = 51.95, P = 0.0140), occupational status (χ² = 9.76, P = 0.0180), income (χ² = 14.72, P = 0.0020), number of sexual partners (χ² = 6.22, P = 0.0130), condom use (χ² = 16.55, P = 0.025), and ignorance (χ² = 7.15, P = 0.0010) were the risk factors associated with trichomoniasis among the study population.Conclusion: The study discovered that the overall prevalence of trichomoniasis in the study population was 23.0% with urine samples having a higher detection rate compared to high vaginal swab samples, though, this may be due to lager urine samples. The pregnant women aged 21-25 years and those in their second trimester of pregnancy had the highest prevalence rates of trichomoniasis. While, marital status, occupation, education, household income, condom use and ignorance were the risk factors associated with trichomoniasis infection. Therefore, there is a need for public health enlightenment to reduce the rate of infection and create more awareness among the study population.
Keywords: Prevalence; risk factors; Trichomoniasis; Pregnant women; AMAC; Nigeria